Estratégias para o avanço do manejo sustentável de águas pluviais urbanas no Brasil - Vasconcelos, Anaí Floriano (2020)
Sustainable urban stormwater management (SUSM) has been studied for some decades and its adoption is growing. However, despite the benefits, its adoption in Brazil is not widespread. Thus, this research aimed to assess the status of SUSM in Brazil and propose strategies for its progress. In this sense, a survey about the SUSM-related barriers in Brazil and the solutions available to their overcoming and effective adoption of SUSM was carried out. Twenty barriers were identified, five of which were considered very important: “Lack of design and maintenance standards”, “Lack of long-term planning”, “Lack of dissemination and knowledge”, “Reluctance to change”, and “Lack of incentives”. The barriers “Lack of capacity or experience” and “Lack of proper laws” also composed the main barriers list, because they are related to all the other barriers investigated. Hence, their overcoming would lead to greater benefits. The search for solutions to the barriers identified eight solution strategies and 80 implementation measures. The solution strategies were correlated with the investigated barriers, providing solutions for overcoming SUSM-related barriers for any location, not only for Brazil. The assessment of the current situation and of the applicability of the strategies/measures to Brazil was carried out through interviews with technical professionals from Brazilian city halls with experience in SUSM (Belo Horizonte – MG, Curitiba – PR, Porto Alegre – RS, Rio de Janeiro – RJ, São Carlos – SP, and São Paulo – SP). Although the municipalities have different experiences, some measures adopted were similar, such as “Runoff quantity control” and “Laws that require SUSM adoption and preservation of pre-development hydrological conditions in new development and renovations”, which were considered easier to be adopted. This led to the conclusion that the experience influences the perception of viability of the measure adoption and, therefore, the resistance to its implementation. Among the experiences of the surveyed cities, some stand out: the recent universalization of the mandatory adoption of SUSM, in Belo Horizonte; the Department of Stormwater Sewers, in Porto Alegre; and the recent search for integration between urban planning and stormwater management, in Belo Horizonte and Porto Alegre. In addition, looking for opportunities for the adoption of SUSM in each city is also recommended. Considering the progress in the whole scenario of SUSM in Brazil, 11 strategies/measures were considered as action opportunities. Their adoption would comprise all the strategies/measures recommended for the overcoming of the barrier “Reluctance to change”, essential for the paradigm shift in the urban stormwater management. Among the action opportunities, the measures "Laws that require SUSM adoption and preservation of pre-development hydrological conditions in new development and renovations" and "Propagation of SUSM" would help to overcome a greater number of barriers and, therefore, should be prioritized. For the progress of SUSM in the country, more studies on the theme should be carried out, especially regarding documentation and sharing of the efforts in SUSM adoption in the Brazilian municipalities.